Analisis Dampak Penerapan Sistem Informasi Manajemen Rumah Sakit dalam Pengambilan Keputusan Manajemen - Kevin Sulay Wijaya; Endang Komara; Kahar Mulyani (Syntax Corporation Indonesia, 2024)
This study aims to analyze the impact of the implementation of the Hospital Management Information System (SIMRS) on management decision-making at Drs. H. Abu Hanifah Hospital, Central Bangka Regency. The research method used is a qualitative method with the PIECES (Performance, Information, Economy, Control, Efficiency, Service) approach. This study involved 17 participants who were directly related to the use of SIMRS in hospitals. The results of the study show that even though SIMRS has been implemented well, there are still several obstacles such as incomplete data that affects employee performance. However, in general, SIMRS has a positive impact on information quality and operational efficiency in management decision-making. Recommendations for improvement include improvements in service aspects and periodic system updates.